Visiting Liya Raya: Liya Togo Tourism Village Managed with Community-Based Tourism Model - La Ode Aris; Heddy Shri Ahimsa-Putra; Pande Made Kutanegara (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2023)
This study analyzes the management of Liya Togo Village as one of the tourist attractions on Wangi-Wangi Island, Wakatobi Regency that implement the Community-Based Tourism (CBT) model. This qualitative research used an ethnographic description, which combined observations and semi-structured interviews with village managers and local communities in the village. The results of this study show that the tourist attraction of Liya Togo Village is managed by CBT Keppo’oli. Local communities are involved in planning, implementing and supervising tourism villages. In addition, CBT Keppo'oli and local communities are involved in marketing the tour packages, being a tour guide, environmental and cultural preservation, and local culinary practices and provision, weaving practices, selling and renting woven sarongs and homestays. Meanwhile, the involvement of the local government is in the form of building facilities and infrastructure and developing tourism human resources of the vilage. The benefits obtained by both the management of Keppo’oli and the local communities are in the form of material benefits such as earning income from various types of businesses and non-material benefits in the form of knowledge, experience, and networking. Meanwhile, there has been no contribution to the government because regulations issued by the government regarding how much contribution CBT Keppo'oli must make to the Wakatobi Regency government are still unobvious. In order to empower the communities in the village, local residents are encouraged to involve in tourism management and programs.